The impact of early social support on subsequent health recovery after a major disaster: A longitudinal analysis - Bonnie Khanh Ha Bui, PhD; Philip Anglewicz, PhD; Mark J. VanLandingham, PhD (SSM: Population Health, 2021)
Social support may facilitate disaster recovery. Prior analyses are hampered by the limits of cross-sectional approaches. We use longitudinal data from the KATIVA-NOLA survey to explore whether social support soon after Hurricane Katrina facilitated recovery of health status for a representative sample of 82 Vietnamese New Orleanians. Health and social support were assessed just before Hurricane Katrina (2005), soon afterwards (2006, 2007), and at longer durations post-disaster (2010, 2018). We use random effects regression to examine how social support measured in 2006 influences mental and physical health measured in 2006, 2007, 2010, and 2018. Social support soon after Katrina was positively associated with physical health and mental health years later in 2010, even after controlling for potential confounders such as Katrina-related housing damage and pre-Katrina health and support and modeling an interaction between year and social support in 2006. Other immigrants who are highly impacted by a major disaster could benefit from programs that seek to rapidly reconstruct systems of social support.